Studi Deskriptif Tentang Karakter Daud Dan Implementasinya Bagi Remaja Masa Kini - Hildegardis Dyna Retno Dumilah; Andreas Joswanto (Sekolah Tinggi Teologi Kalvary - Maluku Utara, 2022)
Adolescence is a transition period from childhood to adulthood. Many problems in the modern world today had become a challenge for teenagers. The rapid development of technology, the influence of social media and the shifting of values in society often made the teenagers confused to determine their attitudes. The influence of social media, materialistic lifestyles, bullying, free sex, misuse of drugs and romance had often become their problems. The author aimed to convey David's character as one of the examples from the Bible to help today's youth become resilient Christian teenagers. This writing used a descriptive-qualitative method, using literature study from the Bible, journals, and books as references. The character of David who always relied on God, prayed and praised God, brave, humble, and rational thinking could set an example of how the youth today should face the problems. By studying David's character, Christian youth are expected to have strong principles and always grow in faith to respond to life and problems well.